Aesthetic perceptions and psychosocial impact of malocclusion: comparison between cleft and non-cleft patients and their parents. (18th April 2018) - Raghavan, Sreevatsan; Philip, Koshi; Batra, Puneet; Marcusson, Agneta
Summary: Objective: To evaluate the influence of dentofacial attractiveness using the 'Psychosocial Impact of Dental Aesthetics Questionnaire' (PIDAQ), Satisfaction with Life Scale (SWLS) and Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN) in patients with cleft lip/palate (CLP), and non-cleft orthodontic patients (Non-CLP) and their parents. Materials and methods: Eighty patients (aged 11–19 years) comprising 40 CLP and 40 non-CLP were administered the PIDAQ and SWLS questionnaires to be rated individually by the patients, along with IOTN-AC rated by the patients and their parents, respectively. The subjects were also sub-divided according to their age, i.e. pre-adolescent and adolescent. Results: The PIDAQ subpart scores for aesthetic concern differed between the two groups, with a significantly ( P < 0.02) lower scoring for the CLP group. The adolescent CLP group scored more negatively than the pre-adolescent group in the dental self-confidence and social impact sub-parts of PIDAQ. No significant differences were observed for satisfaction with life. The parents' IOTN-AC score for both groups was significant ( P < 0.05) greater than the patient's score, especially for adolescent subjects. Limitations: Non-condition specific questionnaires with restrictive sampling sizing and non-inclusion of parameters like stress coping mechanism etc. Conclusion: The parents rated the malocclusion of their child more critically than the child itself. A majority of the CLP group had a problem in identifying themselves using the IOTN-AC as no photo existed depicting a Class III or edge-to-edge malocclusion. Attitudes, especially perceptions of the aesthetics of front teeth, are crucial factors influencing patient's psychological self-concept, social confidence, and treatment need in CLP patients and non-CLP patients, having more relevance as the patient matures towards adolescence and adulthood.